Stem cells and secretome in aplastic anaemia: a bibliometric analysis of global research trends (2018–2023) and future directions for regenerative therapies - Citra Primavita Mayangsari; Harsono Salimo; Yulia Lanti Retno Dewi; Agung Putra; Betty Suryawati; Annang Giri Moelyo (Medicinski glasnik, 2026)
Aim: This study analyzed the research trends related to stem cells and secretome in aplastic anemia between 2018 and 2023 using a bibliometric approach to understand developments and research distribution in this field. Methods: The Scopus database was used to search for relevant articles on aplastic anemia and its relationship to stem cells or secretome, collecting publication and citation data found in article titles, abstracts, and keywords. VOSviewer and Biblioshiny bibliometric software were used to visualize author, country, journal, and keyword networks. Visualization maps aimed to highlight the emergence of words and phrases in titles and abstracts. Results: Based on information from 1,405 articles identified from 2018 to 2023, publication numbers experienced significant fluctuations. Research showed that publications on aplastic anemia, stem cells, or secretome increased by an average of 2.52% annually over the past five years. The most productive country was China with 321 documents, while the most productive institution was the Chinese Academy of Medical Sciences & Peking Union Medical College with 53 documents. We identified four cluster groups: "severe aplastic anemia," "allogeneic stem cell transplantation," "bone marrow failure," and "hematopoietic stem cell transplantation." Conclusion: This study provides a comprehensive overview of research trends in aplastic anemia related to stem cells and secretome from 2018 to 2023, highlighting steady growth and key contributors like China. Future research will likely focus on secretome applications and international collaborations to advance regenerative therapies for aplastic anemia.
Keywords: Aplastic anemia; stem cells; Secretom; Bibliometric